ANALYSIS OF THE INFLUENCE OF LEADERSHIP STYLE AND MOTIVATION ON THE MORALE OF EMPLOYEES OF THE SUB-DISTRICT OFFICE OF BOJONG GEDE BOGOR DISTRICT - Kusumah, Anuraga (Manager : Jurnal Ilmu Manajemen, 2023)
This research was conducted in order to see how far the influence of leadership style and motivation on employee morale in the Bojong Gede District Office, Bogor Regency, by using a questionnaire in data collection. The population and sample in this study were all employees in the Bojong Gede District, totaling 40 employees. Data analysis techniques use validity test, reliability test, classic assumption test and hypothesis test. The test results prove that leadership style and motivation have an effect on employee morale in the Bojong Gede District Office, Bogor Regency, both partially and simultaneously.